2018
DOI: 10.1121/1.5078582
|View full text |Cite
|
Sign up to set email alerts
|

Listening through hearing aids affects spatial perception and speech intelligibility in normal-hearing listeners

Abstract: Cubick and Dau [(2016). Acta Acust. Acust. 102, 547–557] showed that speech reception thresholds (SRTs) in noise, obtained with normal-hearing listeners, were significantly higher with hearing aids (HAs) than without. Some listeners reported a change in their spatial perception of the stimuli due to the HA processing, with auditory images often being broader and closer to the head or even internalized. The current study investigated whether worse speech intelligibility with HAs might be explained by distorted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
5
28
0
Order By: Relevance
“…They found small but significant effects on speech intelligibility across seven HRTFs from the LISTEN database when using a target talker at 0° and two interfering speech sources at ±90°. Cubick et al (2018) measured speech intelligibility in normal-hearing listeners with and without hearing aids. They showed that hearing aids vary the HRTF as well as reduce the spatial benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found small but significant effects on speech intelligibility across seven HRTFs from the LISTEN database when using a target talker at 0° and two interfering speech sources at ±90°. Cubick et al (2018) measured speech intelligibility in normal-hearing listeners with and without hearing aids. They showed that hearing aids vary the HRTF as well as reduce the spatial benefit.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not include head-movements in the headphone condition but did in the loudspeaker condition, rendering direct comparison problematic. Cubick et al (2018) investigated the effect of the microphone placement in hearing aids on speech intelligibility, which affects the HRTF, and showed a reduced spatial benefit in normal-hearing listeners with hearing aids in comparison to a condition without hearing aids. While these studies do suggest an effect of the HRTF on speech intelligibility, no studies have examined this effect in a direct and controlled way.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, it is possible to identify areas where the technical design of the prosthesis, rather than the perceptual limitations of the participant, affects performance. For example, in a speech-intelligibility task, NH listeners were assessed either wearing HAs or unaided (Cubick and Dau, 2016;Cubick et al, 2018). The wearing of high-fidelity HAs appeared to show little or no disadvantage in a co-located masker condition but produced worse performance in a separated masker condition (Cubick et al, 2018) when compared to unaided listening.…”
Section: Introductionmentioning
confidence: 99%
“…When only isolated or impoverished spatial cues are present, auditory localization performance degrades 45 and the natural perception of external auditory objects may even collapse into the listener's head 46 (Baumgartner et al, 2017;Callan et al, 2013;Cubick et al, 2018;Hartmann and Wittenberg, 1996). 47…”
mentioning
confidence: 99%
“…Nevertheless, degraded or isolated ITDs and IIDs still create a strong sense of lateralization within the 48 head; moreover, even highly impoverished spatial cues can be used to achieve spatial release from 49 speech-on-speech masking, behaviorally (Cubick et . More importantly, it is a puzzle as to why realistic and degraded spatial 54 cues yield at best small behavioral differences in masking release even though spatial perception is clearly 55 degraded when cues are impoverished (e.g., Cubick et al, 2018). 56…”
mentioning
confidence: 99%